Case Report: Possible autoimmune obsessive-compulsive disorder with postpartum onset - Endres, Dominique; Hannibal, Luciana; Zaltenbach, Benjamin; Schiele, Miriam A.; Runge, Kimon; Nickel, Kathrin; Berger, Benjamin; Domschke, Katharina; Venhoff, Nils; Prüss, Harald; Tebartz van Elst, Ludger (Frontiers in Immunology, 2022)
Autoimmune obsessive–compulsive disorder (OCD) is rare. The case presented here is that of a female patient in her mid-thirties who developed postpartum OCD. Magnetic resonance imaging showed multiple juxtacortical hyperintensities that may have been post-inflammatory in origin. In tissue-based assays using mouse brain slices, the patient’s cerebrospinal fluid (CSF) showed novel anti-nucleoli autoantibodies in cerebellar Purkinje cells and cortical neurons. The CSF dopamine and glutamate concentrations were dysregulated. The clinical course and diagnostic findings were compatible with possible autoimmune OCD with postpartum onset.